Alternative Corn Processing For Aur Serumpun Farmer Group In Simpang Village, Pasaman District, West Sumatera Province - Syukri, Daimon; Nika Rahma, Yanti; Emil, Salim (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2021)
Background: This activity was carried out in order to transfer corn processing technology to becomea food product that could increase food product diversification in in Simpang village, Pasaman District, WestSumatera Province. Methodology: Tortilla chips as a derivative of corn were introduced through oralpresentations and group discussion forums by the representative team from Andalas University together with“Aur Serumpun” Farmer groups at Simpang village, Pasaman District, West Sumatera Province.Conclusion: Information about corn processing into tortilla chips could be an alternative to multiple thetypes of products that can be produced by the farmer groups “Aur Serumpun”. Recently, they only produceone type of product, namely raw corn products which are directly sold to the animal feed industry. Althoughfarmers were not very enthusiastic, continuous communication with farmers will increase their awareness ofdiversifying maize products that can support their economy in the future.